Using cohort studies to investigate rural and remote mental health - Inder, K; Kelly, B; Berry, H (My University, 2011)
This paper, presented at the 2010 rural health researchers' National Scientific Symposium on Rural and Remote Health, provides an overview of large Australian population mental health cohort studies which have a focus on climate-related and environmental adversity, social factors and mental health. These studies highlight the value of exploiting multiple exceptional datasets to better understand the drivers of rural health, including how to use population-level research to improve health resources in non-metropolitan areas. We show how the key characteristics of rural and remote mental health might be explored by exploiting the following cohort studies: Household, Income and Labour Dynamics in Australia Survey; Australian Rural Mental Health Study; Hunter Community Study; and Extending Treatments, Education and Networks in Depression study. Existing cohort studies that focus on significant rural and regional characteristics can be creatively analysed to better understand geographic variation in mental health. They have the potential to move understanding beyond simple prevalence to building knowledge about the trajectories of psychological distress and determinants of mental disorders and outcomes over time.
Australian Journal of Rural Health
Keywords: Location -- Rural and remote; Health -- Mental; Health and wellbeing; Housing, communities and neighbourhoods; Location; Health; Mental; Rural and remote; Housing, communities and neighbourhoods; Health and wellbeing